THE APPLICATION OF CLINICAL JUDGMENT AND DECISION MAKING OF CRITICAL CARE NURSES IN INTENSIVE CARE UNITS (ICUs): DOI: https://doi.org/10.35654/ijnhs.v2i1.20 - Indah Mei Rahajeng; Faridatul Muslimah (Alta Dharma Publisher, 2019)
Background Intensive Care Unit (ICU) is the hospital setting in which applied specific application of clinical decision making and judgement. The critical patient conditions in ICU may drive nurses to make decision and clinical judgement in short period of time. The approach of clinical decision making which appropriate to be applied in the critical circumstances is important to be identified, thus it could become a guidance for novice and expert critical nurses. Aim The aim of this study was to explain how clinical decision making is applied in Intensive Care Unit (ICU) Method A systematic review of 22 articles was carried out, articles were retrieved from CINAHL, MEDLINE, PUBMED and DISCOVERED databases. The articles were critically reviewed and analized to answer this study’s aim. Result The critically review of the articles were categorized in themes: 1) application of Tanner’s clinical judgment model in ICU, 2) Types of decisions in ICU, 3) Theoretical approach: implementation of decision-making in ICU, 4) Case illustration of decision-making scheme in ICU, 5) Influencing factors of decision-making in ICU, 6) Supporting tools for clinical decision-making in ICU, 7) Understanding of attributes and concepts may enhance the quality of the clinical decision-making process in ICU, 8) Implications for nursing education and practice of understanding clinical decision making in ICU. Conclusions Critical care nurses usually combine different techniques in making decisions; analytical methods including the hypothetic-deductive method, pattern recognition, intuition, narrative thinking, and decision analysis theory are potentially applied. Clinical decision activities in ICU appear in many clinical situations, such as intervention decisions, communication decisions, and evaluation decisions. There are several factors influencing clinical decision-making in intensive care units, including nurses’ experience, the patient’s situation, the layout of the ICU, shift work, inter-professional collaboration practice, physical and personnel resources. The application of clinical decision making could be supported by systematic tools, and the nurses’ knowledge about the concepts and attributes used in ICUs affect their clinical decision-making abilities. Keywords: clicinal decision making, critical care nurse, ICU